The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1007/s11010-014-2086-3
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of response gene to complement 32 (RGC32) induces apoptosis and inhibits cell growth, migration, and invasion in human lung cancer cells

Abstract: Response gene to complement 32 (RGC32) is a novel protein originally identified as a cell cycle activator and has been demonstrated to be overexpressed in a variety of human malignancies, including lung cancer. However, the potential role of RGC32 in lung cancer initiation and progression remains to be elucidated. In the present study, RNA interference mediated by plasmid expressing RGC32 short-hairpin RNA (shRNA) was utilized to knockdown RGC32 expression in human lung cancer LTE cells. We found that the mRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 17 publications
3
24
0
Order By: Relevance
“…RGC32 has been demonstrated to be able to regulate the expression and activities of MMP-2 and MMP-9 [21,22]. In addition, MMPs, Fig.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…RGC32 has been demonstrated to be able to regulate the expression and activities of MMP-2 and MMP-9 [21,22]. In addition, MMPs, Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Accumulating studies have demonstrated that RGC32 expression is dysregulated in human malignancies [16,20]. Recent studies have reported that RGC32 may regulate cancer cell migration and invasion [21,22]. As the human EVT cell line HTR8/SVneo has been widely used to study trophoblast biology [28,29], we further investigated the function of RGC32 in HTR8/SVneo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It plays important roles in the regulation of cell differentiation, angiogenesis, migration, and invasion456. In addition, emerging evidence has revealed that RGC32 is involved in lung cancer7, breast cancer8, hepatic steatosis9, and multiple sclerosis10. However, little is known about its function in CRC.…”
mentioning
confidence: 99%
“…[12][13][14][15][16] A considerable amount of literatures have been published on regulatory effects of RGC-32 in a variety of non-cancerous diseases, concerning vascular diseases, [17][18][19] Alzheimer's Disease, 20 obesity, 21 diabetic retinopathy, 22 autoimmune encephalomyelitis, 23 renal ischemia reperfusion injury, 24 preeclampsia 25 and other non-tumour diseases. In addition to its mediating role in non-cancer, essential roles of it were identified to facilitate the progressions of numerous malignancies, namely ovarian cancer, 26,27 colon cancer, 28,29 prostate cancer, 30 lung cancer, 31,32 breast carcinoma 33 and pancreatic cancer. 34,35 On the contrary, in the literature on Saigusa et al, the relative importance of RGC-32 is debated that RGC-32 emerges as a novel p53-inducible gene, by mediating the arrest of mitotic progression and possible behaves as a tumour-suppressor for glioma.…”
Section: Introductionmentioning
confidence: 99%